Chronic kidney disease and survival following indirect mitral annuloplasty for functional mitral regurgitation - Rottländer, Dennis; Golabkesh, Milad; Degen, Hubertus; Barlagiannis, Dimitrios; Ögütcü, Alev; Saal, Martin; Haude, Michael (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChronic kidney disease is associated with poor prognosis following mitral valve edge-to-edge repair. We aimed to investigate the impact of chronic kidney disease (CKD) on survival in patients with functional mitral regurgitation (FMR) undergoing indirect mitral annuloplasty using the Carillon Mitral Contour System.MethodsIn a retrospective analysis, a total of 100 consecutive FMR patients were assigned according to baseline renal function into three groups: estimated Glomerular Filtration Rate (eGFR) > 60 mL/min/1.73 m2, eGFR 30–59 mL/min/1.73 m2 and eGFR < 30 mL/min/1.73 m2. At 3- and 12-months follow-up after indirect mitral annuloplasty survival, NYHA classification and transthoracic echocardiography were evaluated.Results30 patients revealed a baseline eGFR > 60 mL/min/1.73 m2 (30%), 51 an eGFR 30–59 mL/min/1.73 m2 (51%) and 19 patients an eGFR < 30 mL/min/1.73 m2 (19%). 1-year mortality was significantly higher in eGFR 30–59 mL/min/1.73 m2 and eGFR < 30 mL/min/1.73 m2 compared to a preserved renal function of eGFR > 60 mL/min/1.73 m2 (Log Rank test P value: 0.036). FMR patients with postprocedural acute kidney injury (AKI), defined as an increase in serum creatinine levels ≥0.3 mg/dL within 48 h or ≥1.5 times baseline within 7 days post procedure, showed significantly increased mortality after indirect annuloplasty (Log Rank test P Value: 0.002). Carillon device implantation resulted in FMR reduction and improved NYHA classification at 3- and 12-months follow-up regardless of CKD.ConclusionCKD in patients undergoing indirect mitral annuloplasty seems to be a negative predictor of outcome in FMR patients. However, Carillon device implantation improved NYHA and FMR classification regardless of renal function.